Study on Ultimate Human Evolution: Cooperation of Cerebral and Five-fingernail Development - Kenji Sorimachi (New Visions in Biological Science Vol. 3, 2021)
Contents of the four DNA nucleotides were normalized to investigate biological evolution because these values are derived from the complete genome sequences and are independent of genome size and species. First, it was confirmed that cytosine (C) content calculated from the complete mitochondrial genome reflected biological evolution. Next, the reason why human being (Homo sapiens) whose mitochondrial C content is not the highest among the organisms examined is the most evolved organism has been evaluated. A bird, the pileated woodpecker (Dryocopus pileatus), had the highest C content (0.347) among the present animals examined, and this resulted in the acquirement of wings, which donate the free dimensional behavior in the sky. Cuvier’s dwarf caiman (Paleosuchus palpebrosus) possessed the highest C content among reptiles (0.340) and has acquired hard skin to prevent predation and a strong jaw to catch prey. Among mammalian mitochondrial genomes, orangutans (Pongo abelii and P. pygmaeus) had the highest C contents (0.327 and 0.324, respectively). The C content of humans (Homo sapiens) was 0.313, and those of chimpanzees (Pan troglodytes and P. paniscus) and gorillas (Gorilla gorilla) were 0.307–0.308. The primates with the highest mitochondrial C contents have unique morphological characteristics that represent adaptations to tree-dwelling because they make it possible to escape from ground predators and obtain fruit. In particular, their hand structure consists of five fingers with nails, and the functional and geometrical positions of the thumb relative to the other fingers are extremely important for grasping items such as branches. In addition, human cerebral development might contribute to biological evolution. Thus, the cooperation of manipulative finger function and cerebral development achieved the most complex biological evolution, although human genomic structure does not necessarily reflect this.